Acupuncture combined with language training for aphasia in children with cerebral palsy: a systematic review with meta-analysis and trial sequential analysis - Liu, Shuzhen; Li, Yujiao; Chang, Jun; Shi, Jiangwei; Zhao, Lan (Frontiers in Neurology, 2025)
ObjectiveThe aim of this study was to comprehensively evaluate the efficacy of acupuncture combined with language training in the treatment of aphasia in children with cerebral palsy (CP).MethodsWe searched eight electronic databases from their inceptions to July 1, 2024 for randomized controlled trials (RCTs) of acupuncture for aphasia in children with CP. The evaluation of methodological quality for RCTs incorporated in this study adhered to the guidelines provided by the Cochrane risk-of-bias tool (ROB2). The Grading of Recommendations Assessment, Development and Evaluation Approach (GRADE) was used to evaluate the certainty of evidence of each outcome. The heterogeneity of the included literature was tested using Review Manager 5.4 software, while publication bias was estimated using funnel plots and Egger’s tests by STATA15.1. A trial sequential analysis (TSA) was performed to test the robustness of the conclusiveness of our results.ResultsIn this study, we encompassed a total of 56 randomised controlled trials encompassing 4,683 participants. The majority of these trials were characterized by either a high or uncertain risk of bias, predominantly due to the omission of blinding within their experimental setups. Meta-analysis showed that acupuncture combined with language training was significantly better than language training alone in improving the clinical efficiency (RR: 1.25; 95% CI: 1.21, 1.29; p < 0.00001). A subgroup analysis of the different types of acupuncture revealed that acupuncture, electroacupuncture, scalp acupuncture, and auricular point seed-pressing all showed a significant improvement in aphasia in children with CP. Acupuncture combined with language training could significantly improve the adaptive behaviour (MD: 7.46; 95% CI: 3.67, 11.26; p = 0.0001), verbal behaviour (MD: 7.79; 95% CI: 5.66, 9.92; p < 0.00001), fine motor behaviour (MD: 4.66; 95% CI: 1.28, 8.03; p = 0.007), and personal social behaviour (MD: 6.47; 95% CI: 2.38, 10.55; p = 0.002); it was also significantly more effective in improving the language comprehension developmental quotient (SMD: 2.02; 95% CI: 1.54, 2.50; p < 0.00001), the expressive language development quotient (SMD: 2.40; 95% CI: 1.76, 3.03; p < 0.00001), assessment of dysarthria (MD: 0.40; 95% CI: 0.11, 0.69; p = 0.007), and oral motor function (SMD: 2.63; 95% CI: 1.36, 3.90; p < 0.0001).ConclusionAcupuncture combined with language training could be an effective treatment for aphasia in children with CP. Due to low or very low certainty of evidence and high heterogeneity, more rigorous RCTs are needed to verify the effect of acupuncture in the management of CP.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024501328, identifier CRD42024501328.